Penerapan Algoritma CART Dalam Menentukan Jurusan Siswa di MAN 1 Inhil - Siti Monalisa; Fakhri Hadi (ISB Atma Luhur, 2020)
MAN 1 Inhil is a school that applies ministerial regulations to determine the direction of student majors at the beginning of entry, namely in class X. Determination of majors is done by considering several indicators, namely the results of academic tests, interviews, and student interest. The calculation in determining this course is very simple, namely by adding up the values of each indicator and dividing them together so that an average value is obtained. If the value is fulfilled then the student is grouped based on their interests. This can lead to errors in decision making by the school because it can be subjective because it prioritizes student interests. Therefore we need methods and algorithms to help make decisions well, the decision tree method. One algorithm that can be used is CART algorithm to classify majors with three indicators, namely Natural Sciences, Social Sciences and Religion. The results of this study indicate that the CART algorithm is able to predict correctly, from 360 data classified using the CART algorithm, it can be concluded that 71 data majoring in religion and correctly classified by CART. 144 data majoring in Natural Sciences, 119 data correctly classified and 24 data classified as IPS, and 1 data classified as religion. Of 146 data majoring in social studies, 129 were classified correctly, 16 data were classified as natural sciences. Therefore it can be concluded that CART algorithm has an 80% accuracy so that it can be used in decision making